STUDY OF OXIDANT MDA AND ANTIOXIDANTS SOD AND CATALASE IN PREGNANT & NON-PRENANT WOMEN - Shashi Prabha Singh,Preeti Sharma*,Pradeep Kumar,A.K. Mathur,Tapan Mahapatra (Innovative Journal of Medical and Health Sciences, 2019)
Introduction: Pregnancy is state of dynamic changes in body systems resulting in increased oxygen consumption. Pregnancy is associated with oxidative stress. Reactive oxygen species (ROS), are main causes of oxidative stress (OS) which are generated constantly by external and internal stimuli. ROS causes cellular injury by attacking the phospholipids of cell membranes and reacting with polyunsaturated fatty acids commonly associated with disorders of pregnancy. Aim of this study was to evaluate the level of pro- oxidant and antioxidant in healthy non pregnant and pregnant women. Materials and methods: Parameters of the oxidative status Malondialdehyde and antioxidant Superoxide dismutase and Catalase was estimated in serum of 35 non pregnant and 35 pregnant women in the age group of 20-40 years. Results: Findings were, that there was an increase in Malondialdehyde levels (p<0.0001) and a decrease in superoxide dismutase and catalase activities (P<0.0001 and P<0.0001) in pragnent women significantly. Conclusion: This study shows that there was difference in oxidative status due to dynamic changes in body and circulation that are inherent. During pregnancy oxidative stress is increased that can be fatal to the health of the mother and the fetus. Keywords: Oxidative stress, Antioxidants, Normal pregnancy, Whole blood, Serum, MDA, SOD, Catalase